Keseimbangan Disintegrasi Antara Dana Perimbangan Pusat dan Pemerintah Lokal - Lukman Hakim; Sugianto Sugianto (Universitas Prof. Dr. Moestopo (Beragama), 2017)
Responding to one of the regional autonomy issues of balance funds, financial regulations on this area EAM remains the division of proportion not to giving broad authority so that a greater emphasis on the results of natural resources (SDA) is considered more profitable rich areas (SDA) and unfavorable non-producing areas of natural resources While the general allocation fund resources, although based on a formula that is more objective and transparent, but tend to be more emphasis on equity and less attention to the side of justice. The success of the governments financial problems mengatasai actual area is an important step in moving the wheels of government in the region, but its impact would be potentially to the demands of the financial division more precise, demands federalisasi, up to the threat of disintegration when the central government assessed maintain financial balance in regional centers unfair because it does not take into account the contribution of the region to the central revenue. From some thought it was revealed that in order to anticipate the negative impact of the above then any design other than the financial balance needs to be designed more carefully and take into account regional equity fund balance policy should also always bersendikan central element of the potential capacity of the reception area (assessing the local contribution to revenue centers) as well as guarantee the autonomy regional and local accountability.